The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3168/jds.2018-14582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of winter housing systems on production, economics, body weight, body condition score, and bedding cultures for organic dairy cows

Abstract: Certified-organic dairy cows (n = 268) were used to evaluate the effect of 2 winter (December to April) housing systems on milk production, somatic cell score (SCS), body weight, body condition score (BCS), and economics across 3 winter seasons (2013, 2014, and 2015). Bedding cultures from the housing systems were also evaluated. Cows were randomly assigned to 2 treatments (2 replicates per group): (1) outdoor (straw pack, n = 140) or (2) indoor (3-sided compost bedded pack barn, n = 128). Cows calved during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Most cows were Holstein (72.7%), followed by crossbred (20.5%) and Jersey (6.8%). Studies have reported the use of different breeds of dairy cattle in confinements of the CBP model [ 8 , 45 , 46 , 47 , 48 , 49 ]. The average production of cows (27.2 kg∙day −1 ) in our study was similar to that reported in Kentucky previously (27.3 kg∙day −1 ) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most cows were Holstein (72.7%), followed by crossbred (20.5%) and Jersey (6.8%). Studies have reported the use of different breeds of dairy cattle in confinements of the CBP model [ 8 , 45 , 46 , 47 , 48 , 49 ]. The average production of cows (27.2 kg∙day −1 ) in our study was similar to that reported in Kentucky previously (27.3 kg∙day −1 ) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the study, the Midwestern United States experienced one of the coldest winter seasons on record. The average temperature at the WCROC dairy ranged from −14.4 to 8.9°C (Heins et al, 2019).…”
Section: Experimental Design and Recording Of Datamentioning
confidence: 99%
“…During cold weather, all cows were post-dipped with an approved chlorhexidine powder dip that may have caused more chapped teats than expected during the winter because teats were less conditioned than with a liquid post-dip (Morrill et al, 2019). The absence of a difference between treatments is not surprising, given that both groups were exposed to similar weather and temperatures (Heins et al, 2019)…”
Section: Frostbite and Clinical Mastitismentioning
confidence: 99%
See 2 more Smart Citations